Impact of male partner involvement on mother-to-child transmission of HIV and HIV-free survival among HIV-exposed infants in rural South Africa: Results from a two phase randomised controlled trial - Sifunda, Sibusiso (PLoS One, 2019)
BACKGROUND: The Sub-Saharan Africa region still remains the epicentre of the global HIV/AIDS epidemic. With regards to new paediatric HIV infections, almost 90% of new HIV infections are among children (aged 0–14 years), largely through mother to child transmission. Male Partner Involvement in Prevention of Mother to Child Transmission programmes is now strongly advocated as being key in improving infant outcomes. This study describes the role of Male Partner Involvement on infant HIV infection and mortality survival in the first year among HIV-exposed infants born from HIV positive mothers. METHODS: This study was a two-phase, two condition (intervention or control) longitudinal study as part of a clinic-randomized Prevention of Mother to Child Transmission controlled trial. For Phase 1, female participants were recruited without their male partners. In Phase 2, both female and male participants were enrolled in the study as couples in order to encourage active Male Partner Involvement during pregnancy. Participants had two assessments prenatally (8–24 weeks and 32 weeks) and three assessments postnatally (6 weeks, 6 months, and 12 months) RESULTS: About 1424 women were eligible for recruitment into the study and 18 eligible women declined to participate. All women had a partner; 54% were unmarried, 26% were cohabiting, and 20% were married. Just over half (55%) of the women had been diagnosed with HIV during the current pregnancy. Phase 1 had significantly more HIV-infected infants than Phase 2 at 12-months postpartum (aOR = 4.55 [1.38, 15.07]). Increased depressive symptoms were associated with infant HIV infection at 12-months (aOR = 1.06 [1.01, 1.10]). Phase 1 also had a significantly greater proportion of dead and HIV-infected infants than Phase 2 at 12-months (aOR = 1.98 [1.33, 2.94]). CONCLUSION: Male partner involvement in antenatal care is critical in ensuring infant survival and HIV infection among children born to HIV-positive mothers. This study highlights the high risk of ante-and-post natal depression and underscores the need of screening for depression during pregnancy. TRIAL REGISTRATION: ClinicalTrials.Gov; Trial Number NCT02085356.